Decreasing face touching for children with autism spectrum disorder. (22nd December 2021) - Halbur, Mary; Kodak, Tiffany; McKee, Marisa; Reidy, Jessi; Preas, Elizabeth; Carroll, Regina
Abstract: Face touching is a prevalent behavior for individuals of all ages. However, frequent face touching has potential negative side effects such as the transmission of viruses, bacterial infections, and skin infections. The present investigation extended previous research by evaluating a reinforcement‐based intervention package on the reduction of face touching for children with autism spectrum disorder who tolerated face coverings (i.e., masks, face shields). The treatment package included an unsignaled, momentary differential reinforcement of other behavior procedure with prompts. Results indicated that rates of face touching decreased from baseline levels for all three children during 5‐min treatment sessions. Furthermore, low levels of face touching were observed during follow‐up sessions that were longer in duration (i.e., 15 min) across participants. Results support the utility of behavioral interventions on the reduction of potentially unsafe behaviors related to medical routines.